The practice of nursing research : appraisal, synthesis, and generation of evidence - Grove, Susan K.; Burns, Nancy; Gray, Jennifer , 1955- (Elsevier/Saunders, 2013)
Learn how to properly evaluate and use existing research data and how to conduct your own original research. This authoritative text provides a comprehensive foundation for appraisal, synthesis, and generation of research evidence for clinical nursing practice. This new edition also features enhanced coverage of the research methods most applicable to evidence-based practice (outcomes research, intervention research, and translational research), along with a significant increase in the coverage of qualitative research methodologies.